The Role of Artificial Intelligence in Assessment - Azimov, Fayyozjon G‘ulomjon o‘g‘li (The Lingua Spectrum, 2026)
Artificial Intelligence (AI) has become an essential part of modern educational assessment systems and continues to influence teaching and learning processes worldwide. AI technologies provide innovative approaches for evaluating students’ knowledge, academic performance, and practical skills through automated grading systems, adaptive testing, learning analytics, and personalized feedback. This article examines the role of AI in educational assessment and analyzes its benefits, challenges, and ethical implications. The study highlights that AI-based assessment improves efficiency, accuracy, consistency, and accessibility while supporting individualized learning experiences for students with different educational needs. AI tools also help teachers reduce workload and provide faster feedback to learners. However, several concerns remain significant, including data privacy, algorithmic bias, cybersecurity risks, and excessive dependence on technological systems in education. The article concludes that AI can significantly improve assessment quality and effectiveness when implemented responsibly, ethically, and together with professional human supervision and educational expertise in modern institutions.